Enlarged prints from library microforms : a study of processes, equipment, and materials - Hawken, William R. (Chicago : Library Technology Project, American Library Association, 1963)
In this report, Mr. Hawken provides a similarly careful evaluation intended to assist librarians in the selection of equipment best suited to their needs. The report also identifies those features that make currently available print-out devices unsuited to library purposes, and suggests modifications and improvements which make this equipment more useful to libraries.
aia 16/06/2017
Loans
Keywords: Reader-printers (Microphotography); Photography